In vitro activity of the novel indoloquinone EO-9 and the influence of pH on cytotoxicity. - Phillips, R. M. (Nature Publishing Group, 1992)
The novel indoloquinone compound EO-9 is shortly to undergo phase I clinical evaluation as a potential bioreductive drug. Preclinical studies have shown that EO-9 has greater activity against cells derived from human solid tumours than leukaemias in vitro. The results of this study extend the preclinical data available on EO-9 by demonstrating that EO-9 induces a broad spectrum of activity (IC50 values range from 8 to 590 ng ml-1) against a panel of human and murine tumour cell lines. Some evidence exists of selectivity towards leukaemia and human colon cell lines as opposed to murine colon cells. The response of cells to Mitomycin C were not comparable to EO-9 suggesting that the mechanism of action of these compounds is different. The cytotoxic properties of EO-9 under aerobic conditions are significantly influenced by extracellular pH. Reduction of pH from 7.4 to 5.8 increases cell kill from 40% to 95% in DLD-1 cells. In addition, EO-9 is unstable at acidic pH (T1/2 = 37 min at pH 5.5) compared to neutral pH T1/2 = 6.3 h). The major breakdown product in vitro was identified as EO-5A which proved relatively inactive compared to EO-9 (IC50 = 50 and 0.6 ug ml-1 respectively). These studies suggest that if EO-9 can be delivered to regions of low pH within solid tumours, a therapeutic advantage may be obtained.